EFFECT OF CONCENTRATIONS AND APPLICATION DATES OF - Zuhair A. Dawood (Mesopotamia Journal of Agriculture)
This research was conducted in Horticulture dept., College of Agriculture and Forestry, at Mosul university to test the effect of four concentrations (0, 20, 40, and 60 mg Fe/l) and two dates of application (15/3 and 15/4) of Fe-elements used as a chelating compound Fe-EDTA; on growth, yield and quality of strawberry (Fragaria × ananassa Duch.) Cv. Hapil. A factorial experiment (randomized complete block design) with three replicates, each experimental unit contain ten plants. Data obtained from this experiment was tested by using Duncan’s multiple test at 5% level. The obtained results indicated that there were a significant effect of foliar spray of Fe-EDTA on most growth and yield characteristics, and the most effective treatment was 60 mg Fe/l specially when applied at the first date (15/3) which significantly overtopped in: leaf area, number of runners/plant, dry weight of vegetative growth, total chlorophyll content, number of fruit per plant, average yield per plant and per unit area, total soluble solids and the content of vitamin C as compared with control treatment.